Kekesatan Permukaan Jalan Yang Menggunakan Campuran Ac-Wc Dengan Bahan Tambah Limbah Oleokimia - Wardana, Edward; Sihombing, Atmy Verani Rouly Sihombing (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
Road pavement design must meet roadworthiness requirements to ensure user safety and comfort. One factor is road surface roughness, because low roughness can cause slippery roads and increase the risk of accidents due to vehicle slippage. Road surface roughness testing using the British Pendulum Tester (BPT) is one of the parameters to determine the roughness value. Roadworthiness requirements also apply to asphalt modifications, such as the use of Glycelin Pitch (GP) type oleochemical waste as a substitute for 60/70 pen asphalt. Roadworthiness requirements in this modification are a series of advanced tests, where various tests conducted before paving have been carried out in previous studies and meet the 2018 Bina Marga Technical Specifications Revision 2. This study focuses on road surface roughness testing with the aim of proving that GP can be used as a substitute for penetration asphalt with a content of 27% (GP1) and 14.2% (GP2). The test results showed that the mixture with GP1 provided a higher British Pendulum Number (BPN) value of 80.70 compared to GP2 which was 72.20, while the BPN value for the AC-WC control mixture was 74.50. The average surface temperature in this test was 35.4°C for the GP2 sample and 37.5°C for the GP1 sample. Based on the recommended minimum friction resistance value reference for wet conditions, the GP1 and GP2 mixtures meet the safety requirements for various types of road locations, including locations with high friction such as roundabouts and sharp turns. Thus, the GP mixture shows good potential for application on roads that require high friction, supports traffic safety, and meets road function standards.